2017
DOI: 10.7553/82-2-1626
|View full text |Cite
|
Sign up to set email alerts
|

Trends and patterns of medical and health research at Moi University, Kenya, between 2002 and 2014: an informetrics study

Abstract: Research productivity and visibility are becoming increasingly important in the individual researcher's pursuit to build his or her research reputation, be promoted to the next academic rank within an institution and gain national and international recognition among peers. This paper analyses the research trends and patterns of the academic staff of the College of Health Sciences (CHS) at Moi University in Kenya between 2002 and2014 Conceptual settingResearch productivity and visibility is increasingly becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Their senior rankings (Professor and South African Research Chair, Associate Professor and Professor, respectively) in the university hierarchy and extensive periods of tenure at PLAAS (20, 13 and 20 years, respectively) are likely contributing factors to their high productivity and associated metrics. This finding is consistent with other studies in the literature 7,27 which have found that seniority is a reliable predictor of high metrics.…”
Section: Bibliometric Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…Their senior rankings (Professor and South African Research Chair, Associate Professor and Professor, respectively) in the university hierarchy and extensive periods of tenure at PLAAS (20, 13 and 20 years, respectively) are likely contributing factors to their high productivity and associated metrics. This finding is consistent with other studies in the literature 7,27 which have found that seniority is a reliable predictor of high metrics.…”
Section: Bibliometric Analysissupporting
confidence: 93%
“…It is apparent that all the authors produced almost the same proportion of each kind of output, scholarly and grey literature, the greatest difference being in Hall's outputs which were 44% grey and 56% scholarly literature. has been shown to apply in studies such as that of Rotich and Onyancha 27 . Similarly, in our study, there is evidence in the patterns of author productivity that Lotka's law applies.…”
Section: Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study targeted 20 universities in Nairobi County (4 publics and 16 private) with a total of 237,593 undergraduate students (Rotich & Onyancha, 2016) . Deng et al, (2009) fisher-based formula was adopted to obtain 534 respondents as sample.…”
Section: Methodsmentioning
confidence: 99%
“…Related studies in health and the medical field, specifically focused on bibliometric analysis, has been carried out by Sullivan (2001), Onyancha and Ocholla (2009), Glover and Bowen (2004), Rotich and Onyancha (2016), Chuang, Chuang, Ho and Ho (2011) and Macías-Chapula and Mijangos-Nolasco ( 2002); however, none of these considered HIs as a related field of study. The quantity apportioned to publication of articles in a particular field varies in context, subject and phenomenon.…”
Section: Literature Reviewmentioning
confidence: 99%